Assessment of attitudes towards the use of topical corticosteroids among patients, prescribers and pharmacists in the Republic of Macedonia - Glavas-Dodov, Marija; Simonoska-Crcarevska, Maja; Sulevski, Vanja; Slaveska Raicki, Renata; Starova, Agron (Macedonian Pharmaceutical Association, 2016)
Apart from the time-proven, gold standard treatment of many topical conditions with corticosteroids, the phobia of using topical corticosteroids (TCs) is a phenomenon unveiled among groups of patients, parents, as well as health professionals. Health professionals’ attitude to TCs could have a significant impact on the trend of TCs-phobia among patients. Therefore, it is essential to address this issue as TCs-phobia is something which could also have important implications in medication adherence and compliance to prescribed treatment. Bearing in mind that no survey had been conducted to investigate this matter in Republic of Macedonia (RM), a self-completed questionnaire has been created to assess attitudes and their prevalence associated with TCs-phobia among patients and health professionals with aim to describe the attitude, explore the reasons behind revealed phenomenon and define directions for future interventions needed to advance the healthcare in this field. Our findings show that the TCs-phobia is present among surveyed population (21.6 and 34.22% of all responders expressed negative attitudes or fear of TCs use, respectively). It is also concluded that ~27% of patients on TCs-therapy admitted that they feared of using the medication. However, there is a higher frequency of negative attitudes regarding the use of TCs among the health professionals (~39%) than among patients, where the TCs-phobia is more prominent among non-dermatologists than dermatologists. Moreover, negative attitude and fear of TCs use is universal among paediatricians (73.91%). Portrayed interventions needed to identify and manage the TCs-phobia can lead to improvement of adherence and predicted responsiveness of TCs-therapy.